THE INFLUENCE OF PRAGMATICS ON THE EFFECTIVENESS OF INTERCULTURAL COMMUNICATION BETWEEN MALAY AND JAVANESE - Tri Indah Rizky (JALC : JOURNAL OF APPLIED LINGUISTIC AND STUDIES OF CULTURAL, 2025)
This study explores the influence of pragmatic aspects on the effectiveness of intercultural communication between Malay and Javanese speakers in Indonesia. Although Bahasa Indonesia serves as a shared language, differences in cultural backgrounds lead to variations in pragmatic norms, such as speech acts, politeness strategies, indirectness, and contextual interpretation. Using a qualitative descriptive method involving interviews, observations, and document analysis, the research reveals that Malay speakers tend to be more direct and explicit in their communication, whereas Javanese speakers often prefer indirectness and hierarchical politeness. These differences sometimes result in miscommunication, misinterpretation, and pragmatic failure. However, in contexts of sustained intercultural interaction, both groups show adaptive behaviors and increased pragmatic awareness, which contribute to more effective and respectful communication. The findings highlight the importance of intercultural pragmatic competence and suggest the need for its integration into language education and intercultural training to enhance mutual understanding and harmony in multicultural societies.